Negative impact of high-performance flights on aviators with mitral valve prolapse. Issue 3 (March 2023) - Wand, Ori; Gabbai, Daniel; Epstein Shochet, Gali; Prokupetz, Alex; Kats, Tatiana; Ben-Ari, Oded; Cohen-Hagai, Keren; Gordon, Barak
Abstract: Background: While it appears not to affect healthy aviators' hearts, there are scarce data regarding the impact of high-performance flights on aviators with mitral valve prolapse (MVP). Methods: A retrospective, comparative cohort study of military aviators with MVP. Subjects were categorized to either high-performance (jet fighter) or low-performance (transport and helicopter) aviators. The primary outcomes were the rates of mitral interventions and of adverse cardiovascular events since being an aircrew candidate and up to the end of flying career. Additional outcomes were echocardiographic measurements and the cumulative proportion of mitral valve interventions over time. Results: Of 33 male aviators with MVP, 18 were high-performance aviators. On average, follow-up started at age 18.5 years and lasted 27.8 ± 10.1 years. Baseline characteristics were similar between the study groups. Aviators of high-performance aircraft had increased rates of mitral valve surgery (33 % vs. 0, p = 0.021), MVP-related complications (39 % vs. 6.7 %, p = 0.046), and a higher incidence of mitral valve repair over time ( p = 0.02). High-performance flight was associated with increased intraventricular septum thickness (IVS, 9.7 mm vs 8.9 mm, p = 0.015) and IVS index ( p = 0.026) at the last echocardiographic assessment. High-performance aviators tended to develop worsening severity of mitral regurgitation. Conclusions: High-performance flight may be associated with an increased risk for valvular deterioration and need for mitral surgery in aviators with MVP. Graphical abstract: Unlabelled Image Highlights: High-performance flight has no deleterious effects on hearts of healthy aviators. High-performance flight may result in worsening regurgitation in aviators with mitral valve prolapse (MVP). High-performance aviators with MVP required more mitral surgery.